Estudo descritivo do perfil sociodemográfico da populaçao urbana e rural no estado de Minas Gerais - Freitas Martins Gomes, Nayhara (2017)
This article aimed to understand how variables related to the type of work, income, access to goods, services and information and communication technologies are the profile of families inhabiting the field in Brazil. We used data from the National Household Sample Survey (PNAD), refering to the State of Minas Gerais. It was observed, in terms of final results, that the process of change of the rural way of life is most visible in the consumption-related variables, as regards access to goods and services of urban origin